The hydraulics of open channel flow : an introduction - Chanson, Hubert (London : Arnold, 1999)
This book is about: Basic principles of open channel flows; Introduction to sediment transport in open channels; Hydraulic modelling; Design of hydraulic structures; ...
Keywords: Channels; Channels (Hydraulic engineering)